التعصب العقائدي والمذهبي ، أسبابه النفسية ، طرق معالجته (Journal Of Educational and Psychological Researches, 2016)
In tolerance or ideological fanaticism and religious causes  and ways to treat the psychological            The research aim : to  identify the current  this topic causes psychological  social and  religious intolerance  sectarian and dogmatic ways of treating .Research methodology:  descriptive and analytical.            Define the terms:  intolerance negative :it is the wrong idea plus the accompanying emotion followed by aggressive behavior against  don seconded the idea . Research goals :identify the causes of intolerance and ways to deal with it .Summarized the causes of intolerance psychological follows:• is the feeling of abigot that he is the vicitom as aresult of his frustration.• his personal fanatic is the owner of the troubled personal. • his personal abnormal his mind not only the patient accept the ideas of wrong and belives in strongly .• the presence of atype of personalitiesalbaranuech wrong and believes in the idea of aggressively enthusiastic and overly hatred of the other and refuses to logic.• vent emotional than latlj in self- hatred.            Amaalaj phenomenon of religious intolerance are by appealing to the Quran and sunnah as the constitution of the muslim and mujaahideenhuihui and self-self is self –love and self – interest and dialogue between moderates of isms is very important to follow and objectivity in judging the religious ideas and stay away from hyperbole.